Dielectric properties of solid solutions in the lead zirconate titanate-barium titanate system prepared by a modified mixed-oxide method - Chaisan W. (2014)
Ceramic solid solutions within the system (1 - x)Pb(Zr 0.52Ti0.48)O3-xBaTiO3, where x ranged from 0.0 to 1.0, were prepared by a modified mixed-oxide method. The crystal structure, microstructure and dielectric properties of the ceramics were investigated as a function of composition via X-ray diffraction (XRD), scanning electron microscopy (SEM) and dielectric spectroscopy. While pure BT and PZT ceramics exhibited sharp phase transformation expected for normal ferroelectrics, the (1 - x)PZT-xBT solid solutions showed that with increasing solute concentration (BT or PZT), the phase transformation became more diffuse. This was primarily evidenced by an increased broadness in the dielectric peak, with a maximum peak width occurring at x = 0.4. © 2005 Elsevier B.V. All rights reserved.